Patterns of knowledge and use of tropical plants in homegardens of Southern Morelos, Mexico - Ortiz-Sánchez, Amanda; Romero-Manzanares, Angélica; Monroy-Ortiz, Columba; Luna Cavazos, Mario (Ethnobiology and Conservation, 2023)
The aim of this research is to identify the patterns of use and knowledge of plant species growing in selected tropical homegardens in southern Morelos, Mexico. The method consisted of obtaining informed consent, interviews with homegarden managers, recording socioeconomic data, visits to the interior of each selected homegarden, and personal observations. Data were analyzed through multivariate analyses. The results included a floristic composition (132 species) and eight types of use. Grouping of homegardens by type of use differentiated two main groups: homegardens where principal use is for food plants, and others mainly for ornamental plants. Were found significant differences between homegardens by the number of species and type of use. The grouping of species by number of uses revealed two groups; the patterns of use of plants in homegardens differed according to the user’s preferences; multiuse species were appreciated in group two, which dominated the ornamentals. It was found a significant correlation between age and number of plants known for the owners of the homegardens; while occupation, schooling, and income had no correlation. In conclusion, we rejected the hypothesis of nullity due to differences between richness and the preference of species, the management of homegardens, and by the null influence of the socioeconomic factors studied, with the exception of the age owners and their knowledge of the species.